ASMAUL HUSNA DALAM AL QUR’AN - Mubarok, M.Zaki; Nawawi, Muchlisin; Rahmawati, Nailur (Universitas Negeri Semarang, 2021)
The aims of this study are: (1) to describe the morphological formation of Asmaul Husna; (2) describe the Asmaul Husna slot; (3) describe the Asmaul Husna pattern model; (4) describe the case and the syntactic function of Asmaul Husna; (5) describe the grammatical markers on Asmaul Husna in the Qur'an. This research is an analysis of Asmaul Husna's morphosyntactic in the Qur'an. This research is a qualitative research with library research design. The data of this research are presented with the consideration sample technique. In this study, from 156 data of Asmaul Husna found 3 data ism jamid, and 153 data ism musytaq. There are 91 mubalaghah data slots, 21 ism fa'il data slots, 6 mashdar data slots, and 35 musyabbahah sifah data slots. There are 97 data on raf' cases, 31 data on nashb cases and 33 data on jar cases. There are 2 data as mubtada', 51 data for khabar case, 3 data for fa'il case, 28 data for khabar inna, 10 data for na't (marfu'), and 3 data for ma'thuf (marfu'), 21 data for khabar kana, 2 data as maf'ul bih, 1 data as munada, 6 data as tamyiz, and 1 data as na't (manshub), 8 data as majrur, 5 data as mudhaf ilaih, and 18 data as na't ( majrur), and 2 data as badal (majrur). There were 91 data marked with dhammah dhahirah, and 1 data marked with dhammah muqaddara, 31 data marked with fathah dhahirah, and 33 data marked with kasrah dhahirah. Asmaul Husna merupakan kumpulan 99 nama-nama Allah yang menunjukan keindahan dan keperkasaan Allah. Penelitian ini merupakan analisis morfosintaksis Asmaul Husna di dalam al-Qur’an menggunakan penelitian kualitatif dengan desain studi pustaka (library research). Data penelitian ini disajikan dengan teknik sampel pertimbangan. Dalam penelitian ini, dari 156 data Asmaul Husna ditemukan 3 data ism jamid, dan 153 data ism musytaq. Tedapat 91 data slot mubalaghah, 21 data slot ism fa’il, 6 data slot mashdar, dan 35 data slot sifah musyabbahah. Terdapat 2 data dengan model pola فَعَل, 5 data dengan فَعْل, 4 data dengan فَعِل, 79 data dengan فَعِيْل, 9 data dengan فَعْلَان, 15 data dengan فَعُوْل, 2 data dengan فُعُّوْل, 1 data dengan فَعَال, 17 data dengan فَاعِل, 15 data dengan فَعَّال, 1 data dengan مُفعِل, 1 data dengan مُفَيْعِل, 1 data dengan مُفَعِّل, 1 data dengan مُفْتَعِل 1 data dengan مُتَفَعِّل, dan 1 data dengan مُتَفَاعِل. Terdapat 97 data raf’, 31 data nashb dan 33 data jar. Terdapat 2 data sebagai mubtada’, 51 data khabar, 3 data fa’il, 28 data sebagai khabar inna, 10 data na’t (marfu’),dan 3 data ma’thuf (marfu’), 21 data khabar kana, 2 data maf’ul bih, 1 data munada, 6 data tamyiz, dan 1 data na’t (manshub), 8 data majrur, 5 data mudhaf ilaih, dan 18 data na’t (majrur), dan 2 data badal (majrur). Ditemukan 91 data berpenanda dhammah dhahirah, dan 1 data berpenanda dhammah muqaddarah, 31 data berpenanda fathah dhahirah, dan 33 data berpenanda kasrah dhahirah.